The Tootin' Louie : A History of the Minneapolis and St. Louis Railway - Hofsommer, Donovan L. (Book collections on Project MUSE., 2005)
In The Tootin' Louie, railroad historian Don L. Hofsommer offers a comprehensive biography of the Minneapolis & St. Louis Railway and its Minnesota, Iowa, South Dakota, and Illinois service areas. Incorporating primary research documents, including station records and dispatchers' reports, Hofsommer brings the M & StL to life by portraying the lives and times of the people involved in the railroad.